Biomolecular Mechanism of Herbal Medicine on Muscle Atrophy in Type 2 Diabetes Mellitus Rats: Systematic Review - Kuswandi, Asep; Ikram, NKK; Muchtaridi, Muchtaridi (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Musculoskeletal atrophy causes an increase in advanced glycation end products, a proinflammatory phenotype, and oxidative stress, which can lead to micro- and macrovascular complications.This can cause loss of skeletal muscle mass, strength, and function, potentially leading to sarcopenia. Herbal medicines have been proven to be able to treat various diseases in humans, herbal medicines have the potential to increase skeletal muscle mass. There are various genes that have been induced by herbal medicines to prevent muscle atrophy in chronic diseases. It is necessary to explain the molecular mechanisms of the role of herbal medicines in preventing muscle atrophy due to chronic diseases. This study explores the biomolecular mechanisms of each herbal medicine based on the pathways of inflammation, protein synthesis, apoptosis, autophagy, and glucose uptake in T2DM mice. The research results show that herbal medicine can potentially activate 81 gene expressions that can prevent muscle atrophy in T2DM mouse models. Keywords: biomolecular, herbal medicine, musculoskeletal atrophy, type 2 diabetes